2018
DOI: 10.1148/radiol.2017170896
|View full text |Cite
|
Sign up to set email alerts
|

Intermanufacturer Comparison of Dual-Energy CT Iodine Quantification and Monochromatic Attenuation: A Phantom Study

Abstract: Purpose To determine the accuracy of dual-energy computed tomographic (CT) quantitation in a phantom system comparing fast kilovolt peak-switching, dual-source, split-filter, sequential-scanning, and dual-layer detector systems. Materials and Methods A large elliptical phantom containing iodine (2, 5, and 15 mg/mL), simulated contrast material-enhanced blood, and soft-tissue inserts with known elemental compositions was scanned three to five times with seven dual-energy CT systems and a total of 10 kilovolt pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
132
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(147 citation statements)
references
References 22 publications
13
132
1
1
Order By: Relevance
“…This finding is consistent with other authors who found inferior performance of the Twinbeam system for virtual monoenergetic and virtual noncontrast imaging. 50,51 Using images with reduced stopping power uncertainty could allow for reduced margins when designing treatment plans, possibly opening pathways to dose escalation and increased organ-at-risk sparing. 52 If dose could be calculated on daily CBCT using the proposed method, the margins typically added for setup uncertainties could be reduced since the patient would not be moved between "simulation" and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other authors who found inferior performance of the Twinbeam system for virtual monoenergetic and virtual noncontrast imaging. 50,51 Using images with reduced stopping power uncertainty could allow for reduced margins when designing treatment plans, possibly opening pathways to dose escalation and increased organ-at-risk sparing. 52 If dose could be calculated on daily CBCT using the proposed method, the margins typically added for setup uncertainties could be reduced since the patient would not be moved between "simulation" and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…142 Furthermore, CT numbers from virtual monoenergetic images are accurate to within 10 HU across different CT scanner models from different CT scanner manufacturers. 143 These desirable properties reduce variations in the calculation of SPR values.…”
Section: B5 Creation Of Electron Density and Effective Atomic Nummentioning
confidence: 99%
“…In our study, we found that across all 10 DECT scanners, iodine quantification errors were reported to be within 5%–10%, corresponding to ±0.3 and ±1.5 mg/mL for the 2 and 15 mg/mL inserts, respectively. This low error and the low dependence on the technique parameters investigated, suggest that iodine density maps may be used in a quantitative manner for clinically relevant iodine concentrations regardless of the technique parameters used …”
Section: Discussionmentioning
confidence: 99%
“…Iodine quantification error was also shown to increase with increasing phantom size; however, this effect has been disputed by other studies . Evaluation of the CT number stability for monoenergetic reconstructions has shown dependence on phantom size, as well as greater inaccuracies for dense materials in low keV reconstructions . This effect may be due to suboptimal correction of beam hardening effects for these energies.…”
Section: Introductionmentioning
confidence: 99%